In Hebrews the Marine Animals Ascendency (Plesiosuchus / Steneosaurus Ancestor) – « Adam's Broken Rib » in the Genesis – and West African Peoples - Pirot, Florent (European Journal of Applied Sciences, 2021)
Abstract : this demonstration correlates with traditional theorems of life emerging through water.